Role of artificial intelligence in haematolymphoid diagnostics - Syrykh, Charlotte; Brand, Michiel; Kather, Jakob Nikolas; Laurent, Camille (Histopathology, 2025)
The advent of digital pathology and the deployment of high‐throughput molecular techniques are generating an unprecedented mass of data. Thanks to advances in computational sciences, artificial intelligence (AI) approaches represent a promising avenue for extracting relevant information from complex data structures. From diagnostic assistance to powerful research tools, the potential fields of application of machine learning techniques in pathology are vast and constitute the subject of considerable research work. The aim of this article is to provide an overview of the potential applications of AI in the field of haematopathology and to define the role that these emerging technologies could play in our laboratories in the short to medium term. Workflows of artificial intelligence implementations in haematopathology from diagnostic assistance tools (A) to exploratory approaches (B).